Should Vasopressors Be Started Early in Septic Shock? - Cioccari, Luca; Jakob, Stephan M.; Takala, Jukka (Seminars in Respiratory and Critical Care Medicine, 2021)
Sepsis can influence blood volume, its distribution, vascular tone, and cardiac function. Persistent hypotension or the need for vasopressors after volume resuscitation is part of the definition of septic shock. Since increased positive fluid balance has been associated with increased morbidity and mortality in sepsis, timing of vasopressors in the treatment of septic shock seems crucial. However, conclusive evidence on timing and sequence of interventions with the goal to restore tissue perfusion is lacking. The aim of this narrative review is to depict the pathophysiology of hypotension in sepsis, evaluate how common interventions to treat hypotension interfere with physiology, and to give a resume of the results from clinical studies focusing on targets and timing of vasopressor in sepsis. The majority of studies comparing early versus late administration of vasopressors in septic shock are rather small, single-center, and retrospective. The range of “early” is between 1 and 12 hours. The available studies suggest a mean arterial pressure of 60 to 65 mm Hg as a threshold for increased risk of morbidity and mortality, whereas higher blood pressure targets do not seem to add further benefits. The data, albeit mostly from observational studies, speak for combining vasopressors with fluids rather “early” in the treatment of septic shock (within a 0–3-hour window). Nevertheless, the optimal resuscitation strategy should take into account the source of infection, the pathophysiology, the time and clinical course preceding the diagnosis of sepsis, and also comorbidities and sepsis-induced organ dysfunction.
Keywords: sepsis; vasopressor agents; blood volume; intravenous infusions; blood pressure; hypotension